Process optimization and economic evaluation of air gasification of Saudi Arabian date palm fronds for H2-rich syngas using response surface methodology - Ali, A.M. (Elsevier Ltd, 2022)
The transition of energy extraction from the fossil fuel to renewable energy is a primary drive-in world. Saudi Arabia is one of the big producer of date fruit which generates an abundant amount of date palm wastes. There is no proper utilization of these wastes in Saudi Arabia. Conversion of date palm waste into energy is a major potential alternative source of bioenergy via gasification. In current study, process optimization and economic evaluation of air gasification of date palm fronds (DPF) has been performed in downdraft gasifier for energy conversion. The impact of three process parameters temperature, air flowrate, and feedstock particle size on gas composition were investigated. The response surface methodology (RSM) was adopted for experimental design, optimization, and individual and interactive effects of parameters on H2 and CO compositions to find their optimum values. Temperature is the most influencing factor for H2 composition and it varies from 6 vol to 18 vol which is higher compared to air flowrate and feedstock particle size. A similar pattern of influencing factors was observed for CO composition it varies from 8 vol to 20 vol. The enrichment of H2 and CO is due to the activation of endothermic reactions at elevated temperature. On the other hand, factor influencing order for CO2 composition as feedstock particle size > air flowrate > temperature. The optimum conditions were found 900â temperature, 1 l/min air flowrate, and 6 mm feedstock particle size to maximizing the H2 and CO compositions. Cost of syngas produced from air gasification of DPF was determined SAR 4.04/kg which can be minimized to scale-up the gasification system. DPF conversion into energy is environmentally friendly alternative source of renewable energy that will helps to reduce the dependency on fossil fuel. Â© 2022 Elsevier Ltd